Building Technology-Based Islamic Education Learning: A Review of Learning Principles, Behaviorism, and Cognitivism - Ikhsan, Muhammad (Jurnal Hadratul Madaniyah, 2026)
Abstracts Technological developments in education have not been fully integrated optimally in Islamic Religious Education (PAI) learning, resulting in a gap between the needs of 21st-century learning and learning practices that are still predominantly teacher-centered. This condition encourages the need for an in-depth study of how learning principles and theories of behaviorism and cognitivism can be used as a basis for designing effective technology-based PAI learning. This study aims to analyze the integration of these learning theories as a basis for developing a more comprehensive technology-based PAI learning model. The study uses a library research approach by reviewing journals, books, and relevant research results, which are analyzed through content analysis techniques to identify conceptual patterns, similarities, and theoretical contributions. The results show that learning principles such as subsumption, progressive differentiation, and integrative reconciliation can strengthen the structure of digital PAI materials; behaviorism theory plays a role in designing technological features that are reinforcement and form religious habits; while cognitivism theory supports the development of digital media that facilitate information processing and meaningful learning. The conclusion of the study confirms that the integration of these three theoretical foundations can produce a technology-based PAI learning model that is more interactive, adaptive, and pedagogical. This study contributes to the development of a technology-based PAI conceptual framework and recommends empirical testing of the model's effectiveness through further research.